Improvement of Phosphorus Use Efficiency in Rice by Adopting Image-Based Phenotyping and Tolerant Indices - Bhatta, Bishal Binaya; Panda, Rajendra Kumar; Anandan, Annamalai; Pradhan, Nirakar Susanta Narayan; Mahender, Anumalla; Rout, Kumbha Karna; Patra, Bhaskar Chandra; Ali, Jauhar (Frontiers in Plant Science, 2021)
Phosphorus (P) is one of the second most important nutrients for plant growth and development, and its importance has been realized from its role in various chains of reactions leading to better crop dynamics accompanied by optimum yield. Yet, injudicious use of P and non-renewability across the globe severely limits agricultural crop production, including rice. The development of P efficient cultivar can be achieved by screening genotypes either by destructive or non-destructive approach. Exploring image-based phenotyping (shoot and root) and tolerant indices in conjunction under low P was the first report, the epicenter of our study. Eighteen genotypes were selected for hydroponic study from the soil-based screening of 68 genotypes to identify the traits through non-destructive (geometric traits by imaging) and destructive (morphology and physiology) techniques. The geometric traits such as minimum enclosing circle, convex hull, and caliper length are shown promising responses in addition to morphological and physiological traits. In 28 day old seedlings, leaves positioned from 3rd to 5th played a crucial role in P mobilization to different plant parts and maintains plant architecture under P deficient conditions. Besides, reduced leaf angle adjusted due to a decline in leaf biomass was observed. Concomitantly, these geometric traits facilitate the evaluation of low P tolerant rice cultivars at an earlier stage, accompanying several stress indices. Out of which, Mean Productivity Index, Mean Relative Performance, and Relative Efficiency index utilizing image-based traits displayed better response in identifying tolerant genotypes under low P condition. This study signifies the importance of image-based phenotyping techniques to identify the potential donors and improving P use efficiency in modern rice breeding programs.